Continuous Dependence for a Backward Parabolic Problem (Journal of Partial Differential Equations, 2003)
" We consider a backward parabolic problem arising in the description of the behavior of the toroidal part of the magenetic field in a dynamo problem. In our backward time problem, the media parameters are spatial distributed and the boundary conditions are of the Robin type. For this ill-posed problem, we prove that the solution depends continuously on the initial-time geometry."
Keywords: Parabolic equation; inverse problem; stability